2019
DOI: 10.1016/j.jsha.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular function after successful revascularization for acute anterior myocardial infarction without right ventricular infarction by echocardiography

Abstract: Background Right ventricular (RV) involvement in acute left ventricular (LV) myocardial infarction (MI) is frequently underestimated in the clinical setting owing to the diagnostic limitations of the electrocardiogram and echocardiography. Objective To assess RV function in patients presented with first acute anterior ST elevation myocardial infarction (STEMI) who underwent successful primary percutaneous coronary intervention (PCI) and factors affecting it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In contrast to other research, Abdeltawab et al (14) attributed this to patients who were on average 45.9+7.6 years younger, which is why when comparing both groups' normal and poor RV performance, the influence of age becomes apparent in comparison with their population. Regarding sex or DM, HTN, or hyperlipidemia, there was no statistically significant difference between the groups.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast to other research, Abdeltawab et al (14) attributed this to patients who were on average 45.9+7.6 years younger, which is why when comparing both groups' normal and poor RV performance, the influence of age becomes apparent in comparison with their population. Regarding sex or DM, HTN, or hyperlipidemia, there was no statistically significant difference between the groups.…”
Section: Discussionmentioning
confidence: 60%
“…They, however, failed to define the time of echocardiography after ASTEMI, and they used an echocardiography modality that was not only dependent on the ultrasound beam angle but also associated with low spatial resolution, high noise, and interobserver variability [ 27 ]. Still, it seems that echocardiography was not capable of detecting this damage to the RV in all patients with ASTEMI [ 28 , 29 ]. Similar to Nourian et al, we found that RA reservoir and conduit functions were impaired in patients with ASTEMI, while we detected no significant impairment in RV function in the same phase.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable data on RV damage using cardiac magnetic resonance imaging (MRI) are scarce. 12 The association between right ventricular functional parameters and STEMI [12][13][14][15][16] was previously examined. Morbidity and mortality are well known to be associated with right ventricular (RV) involvement after an acute myocardial infarction (MI).…”
Section: Discussionmentioning
confidence: 99%